Motivating the development of a virtual process chain for sheet molding compound composites. Issue 1 (18th November 2019) - Görthofer, Johannes; Meyer, Nils; Pallicity, Tarkes Dora; Schöttl, Ludwig; Trauth, Anna; Schemmann, Malte; Hohberg, Martin; Pinter, Pascal; Elsner, Peter; Henning, Frank; Hrymak, Andrew; Seelig, Thomas; et al.
Abstract: This contribution presents a physical process chain and the corresponding virtual process chain for sheet molding compound (SMC) composites. Here, focus lies on the physical process chain as a motivation for the virtual process chain as discussed in the authors' publication [1]. The key steps of the virtual process chain are the identification of initial and boundary conditions, the compression molding simulation, the mapping of data and the structural simulation. The so established virtual process chain is validated via experimental investigations on a demonstrator structure. Both, the predicted results of the compression molding simulation, as well as the results of the structural simulation are in good accordance with the experiments.